Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1068/i0484
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Judgment of Triangular Shape: Compactness and Not the Golden Ratio Determines Perceived Attractiveness

Abstract: Many studies over a period of more than a century have investigated the influence of the golden ratio on perceived geometric beauty. Surprisingly, very few of these studies used triangular shapes. In Experiment 1, we presented right triangles that differed in regard to their elongation determined by increasing the length of one side relative to another. Attractiveness ratings did not peak at the golden ratio, but there was a very strong influence of axis ratio overall. Participant ratings were a negative decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…As mentioned in the Introduction, already Pierce (1894) observed that perceptual stability is a variant of balance, especially for vertically arranged elements in a picture. More recently, Friedenberg (2012) even proposed a perceptual instability hypothesis, stating that objects perceived as more fragile are less attractive.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in the Introduction, already Pierce (1894) observed that perceptual stability is a variant of balance, especially for vertically arranged elements in a picture. More recently, Friedenberg (2012) even proposed a perceptual instability hypothesis, stating that objects perceived as more fragile are less attractive.…”
Section: Methodsmentioning
confidence: 99%
“…Email: wenwen@asu.edu W. Li et al retrieval, this factor is used to identify shape signatures for non-rigid shape search and retrieval in large databases (Ovsjanikov et al 2009). In psychological studies, compactness has been introduced to quantify perceptual stability and to understand the causes of perceived shape aesthetics (Friedenberg 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These are commonly found in constructed objects like houses and so familiarity may explain its ranking. In previous work, we have found that participants rate right triangles that are more compact more beautiful and familiarity may account for the result (Friedenberg, 2012).…”
Section: Discussionmentioning
confidence: 71%